Foodbank of Western Australia’s Healthy Food for All - Butcher, L.; Chester, M.; Aberle, L.; Bobongie, V.; Davies, C.; Godrich, S.; Milligan, R.; Tartaglia, J.; Thorne, L.; Begley, Andrea (Emerald Group Publishing Limited, 2014)
Purpose – In Australia, the Foodbank of Western Australia (Foodbank WA) has a reputation for being at the forefront of health promotion. The purpose of this paper is to describe Foodbank WA’s innovative food bank plus approach of incorporating healthy lifestyle initiatives (i.e. nutrition and physical activity education) into its core food bank business, so as to target priority issues such as food insecurity, poor food literacy, overweight, obesity, poor nutrition and physical inactivity.Design/methodology/approach – A case study approach was utilised to explore Foodbank WA’s Healthy Food for Alls(HFFA) strategy. HFFA is a comprehensive state wide, school and community based strategy, including the School Breakfast Programme, Food Sensationss and Choose to Move initiatives, designed to promote healthy lifestyles to low socioeconomic and vulnerable groups – a major target group of food banks.Findings – Since its inception in 2007, the delivery of food, education and resources has increased across all of Foodbank WA’s HFFA initiatives. Evaluation results from feedback surveys demonstratethe success of these interventions to positively impact upon food security, health and wellbeing ofparticipants.Originality/value – HFFA is a unique, effective and novel strategy that addresses a number of healthand nutrition issues. Food banks are well placed to deliver food literacy and healthy lifestyle initiatives.Foodbank WA’s holistic approach and demonstrated success provides other food banks with a bestpractice model and knowledge base for the development of similar health promotion strategies andinterventions.